Perspektif Pemimpin Guru Informal tentang Pendidikan Toleransi: Pembelajaran dari Toleransi Salib Yohanes Calvin - Anselmus Dami, Zummy; Novi Styorini, Indyah (STT Reformed Injili Internasional, 2024)
The study aimed to criticize the weaknesses of the concept of tolerance education and analyze the components and concepts of John Calvin's cross-tolerance, which are used to strengthen and complement the perspective of teachers as informal leaders on tolerance education. The research method used is qualitative with a content analysis approach. The results of the current study found four main themes including the conceptual definition of tolerance, the dimensions of tolerance, the virtues of tolerance and the limits of tolerance. Cross tolerance teaches teachers as informal leaders that patience will not take root in humanity if there is no deep sorrow for evil and injustice to bear (a prerequisite for tolerance), doctrine and worship of God must be properly maintained to protect tolerance, and obedience to God is the mother and guardian of all virtues (including tolerance education). Thus, teachers as informal leaders in schools should not tolerate contamination of divine justice and true justice within the framework of a broader and fundamental virtue mindset.